'We are the people whose opinions don't matter'. A photovoice study exploring challenges faced by community health workers in Uganda. Issue 3 (3rd March 2020) - O'Donovan, James; Hamala, Rebecca; Namanda, Allan Saul; Musoke, David; Ssemugabo, Charles; Winters, Niall
ABSTRACT: Understanding the experiences of community health workers (CHWs) through the use of participatory visual methods (PVMs) has been relatively underexplored. One such PVM is photovoice, which involves the capture of photographic images related to issues of social importance. In this study, we explore challenges faced by eight CHWs in Mukono District, Uganda through the use of photovoice. Over a six-week period, CHWs captured 62 relevant photographs. Subsequent individual interviews and group discussions were held with the CHWs regarding the content of the photographs. Using traditional content analysis, a range of themes related to perceived challenges faced by the CHWs were highlighted, including poor infrastructure, insufficient on-going training and supervision, relationships with other health professionals and equipment supplies. Suggestions were raised as to why such challenges existed and how they could be addressed; mainly through increased roles of the government and supporting NGOs. Overall, photovoice was generally a feasible method to highlight the challenges faced by CHWs, however community acceptability regarding image capture and consent taking may prove challenging, given past historical experiences. The use of photovoice in this study highlighted the need to address the multiple and complex challenges faced by CHWs in order to help them fulfil their roles.